Antimicrobial Efficiency of Chitosan and Its Methylated Derivative against Lentilactobacillus parabuchneri Biofilms - Diellza Bajrami; Stephan Fischer; Holger Barth; Syed Imdadul Hossain; Nicola Cioffi; Boris Mizaikoff (Molecules, 2022)
Antimicrobial materials are considered potential alternatives to prevent the development of biofilm-associated contaminations. Concerns regarding synthetic preservatives necessitate the development of innovative and safe natural antimicrobials. In the present study, we discuss the in situ infrared attenuated total reflection spectroscopy (IR-ATR) investigations of the selective antimicrobial efficiency of chitosan in controlling the growth of Lentilactobacillus parabuchneri biofilms. The protonated charges of chitosan were additionally amplified by structural modification via methylation, yielding quaternized derivative TMC (i.e., N, N, N-trimethyl chitosan). To evaluate antimicrobial effectiveness against L. parab. biofilms, IR-ATR spectroscopy provided information on molecular mechanisms and insights into chemical changes during real-time biofilm inhibition studies. The integrated fiberoptic oxygen microsensors enabled monitoring oxygen (O2) concentration gradients within biofilms, thereby confirming the metabolic oxygen depletion dropping from 4.5 to 0.7 mg L−1. IR studies revealed strong electrostatic interactions between chitosan/its water-soluble derivative and bacteria, indicating that a few hours were sufficient to affect biofilm disruption. The significant decrease in the IR bands is related to the characteristic spectral information of amide I, II, III, nucleic acid, and extracellular polymeric matrix (EPS) produced by L. parabuchneri biofilms. Cell clusters of biofilms, microcolonies, and destabilization of the EPS matrix after the addition of biopolymers were visualized using optical microscopy. In addition, scanning electron microscopy (SEM) of biofilms grown on polystyrene and stainless-steel surfaces was used to examine morphological changes, indicating the disintegration of the biofilm matrix into individual cells. Quantification of the total biofilm formation correlated with the CV assay results, indicating cell death and lysis. The electrostatic interactions between chitosan and the bacterial cell wall typically occur between protonated amino groups and negatively charged phospholipids, which promote permeabilization. Biofilm growth inhibition was assessed by a viability assay for a period of 72 h and in the range of low MIC values (varying 0.01–2%). These results support the potential of chitosan and TMC for bacterial growth prevention of the foodborne contaminant L. parabuchneri in the dairy industry and for further implementation in food packaging.